2003
DOI: 10.14507/epaa.v11n41.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Full and Alternative Day Block Scheduling on Language Arts and Science Achievement in a Junior High School

Abstract: The effects of a full (4 X 4) block scheduling program and an alternate day (AB) block scheduling program in a junior high school were under investigation in this study through the use of an ex post facto, matched sampling design. Measures investigated were standardized achievement tests in science and language arts. Both forms of block scheduling had been in place for several years, and one teacher in science and one teacher in language arts had taught students under both forms of scheduling. Because the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
4
4
0
Order By: Relevance
“…Additional, the A/B 45-60 minute yearlong schedule had the lowest performance level. While the research literature addressing the relationship of achievement and A/B flexible scheduling impacts is sparse with regard to middle-level high-stakes testing scenarios, the findings of the present study support those of similar studies (Gainey & Brucato, 1999;Lewis et al, 2003). Evidence that longer instructional periods fail to adequately support average attention spans or the retention of general knowledge in core areas (Gould, 2003) supports the present study's finding that the schedule with the greatest amount of instructional time allocated to social studies (80-90 minute yearlong block) has the lowest achievement levels of all schedule configuration types.…”
Section: Research Questionsupporting
confidence: 88%
“…Additional, the A/B 45-60 minute yearlong schedule had the lowest performance level. While the research literature addressing the relationship of achievement and A/B flexible scheduling impacts is sparse with regard to middle-level high-stakes testing scenarios, the findings of the present study support those of similar studies (Gainey & Brucato, 1999;Lewis et al, 2003). Evidence that longer instructional periods fail to adequately support average attention spans or the retention of general knowledge in core areas (Gould, 2003) supports the present study's finding that the schedule with the greatest amount of instructional time allocated to social studies (80-90 minute yearlong block) has the lowest achievement levels of all schedule configuration types.…”
Section: Research Questionsupporting
confidence: 88%
“…Nichols (2005) applied a pre-/post-design during the process of conversion from traditional to block schedules but found little evidence to support the hypothesis that conversion to block scheduled formats would significant affect students' achievement. Lewis et al (2003) criticise the inconsistency of the literature dealing with achievement differences, but they concluded that, consistently, block scheduling was not worse compared to traditional instruction. Our results do comply with these findings but we applied an educational treatment rather than an investigation of entire schools.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, however, revealed contrasting results. Some authors found support for block scheduling which resulted in higher achievement (Carroll 1994;Kahzzaka 1997;Deuel 1999;Knight and DeLeon 1999;Lewis et al 2003), and others not (Bateson 1990;Lockwood 1995;Lawrence and MacPherson 2000;Nichols 2005). This seems the case particularly in subjects that might require some repeated instruction, like maths or science (Marchant and Paulson 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By spanning a minimum of 2 years, the data collection approach allowed for the stabilization and measurement of an intervention effect (Lewis et al, 2003). The data collected for this study were unique in that ninth graders from the 2000-01 school year were one of the last cohorts to be exposed to the same type of scheduling format in their feederjunior high school as in their senior high school.…”
Section: Data Collectionmentioning
confidence: 99%